Consumption pattern of selected petroleum products - National Council of Applied Economic Research (New Delhi : National Council of Applied Economic Research, 1971)
The book covers field study, transport, agriculture, fisheries, power, industries, lubricants, bitumen, wax, and summing UP. The major objective of this study is to provide a basis for a continuous compilation of data on the consumption of selected petroleum products on a year to year basis.
Includes bibliographical references and index.
rpm 22/01/2019
Loans
Keywords: Petroleum industry and trade; Petroleum products; Consumption (Economics)